A Case of Epstein-Barr Virus–Associated Leiomyosarcoma Concurrently With Posttransplant Lymphoproliferative Disorders After Renal Transplantation. Issue 12 (July 2019) - Aida, Naohiro; Ito, Taihei; Maruyama, Michihiro; Saigo, Kenichi; Akutsu, Naotake; Aoyama, Hiromichi; Kitamura, Hiroshi; Kenmochi, Takashi
Epstein-Barr virus (EBV) infection might induce not only posttransplantation lymphoproliferative disorder (PTLD) but also leiomyosarcoma. We report a case of EBV-associated leiomyosarcoma concurrently with PTLD after renal transplantation. The patient was a 30-year-old woman who underwent living donor kidney transplantation at 27 years of age. Preoperative EBV viral capsid antibody immunoglobulin M, immunoglobulin G (IgG), and EBV nuclear antigen IgG were negative. Multiple lung and liver tumors were detected 1.5 years after transplantation. She was diagnosed with PTLD after tumor biopsy. Her EBV DNA was 110 copies/mL detected by real-time polymerase chain reaction when PTLD was diagnosed. She received dose reduction of immunosuppressive therapy and several chemotherapies. Because her hepatic lesion was still progressive while pulmonary lesion was reduced, a liver tumor biopsy was performed, but the biopsy specimens were necrotic. A left lateral segmentectomy was performed as a third biopsy for treatment-resistant hepatic lesion 2.5 years after her first PTLD diagnosis. Pathologically, she was diagnosed with EBV-associated leiomyosarcoma. She was treated with sirolimus, but died 7 months after the operation. This is the first case of the coincidence of leiomyosarcoma associated with EBV and PTLD. This case was exceedingly rare; however, we must consider the coincidence of leiomyosarcoma associated with EBV and PTLD when encountering treatment-resistant PTLD.